Implementation of the Make A Match Learning Model in Student Learning Activities for Theme 8 Subtheme 2 Learning 3 in Class IV of SD Negeri 53 Banda Aceh - Jannah, Miftahul; Yamin, M.; Fitri, Aida (Elementary Education Research, 2024)
Learning model is an alternative used by teachers to facilitate knowledge transfer activities and ensure that learning activities occur as effectively as possible. The Make a Match model is one learning approach that can be applied in learning process. The Make a match learning model can draw students' attention and encourage them to participate in the learning process by looking for pairs of cards while learning about relevant topic in a fun atmosphere. By using the Make a match learning model, students will be more courageous in expressing their thoughts and will find it easier to understand the information which will encourage student participation. This research aims to describe how is the application of the Make A Match learning model to the learning activities of students studying theme 8 subtheme 2 PB 3 in class IV at SD Negeri 53 Banda Aceh. This study employed a qualitative methodology using a descriptive research design. The subjects of this research were class IVA teachers and class IVA students at SD Negeri 53 Banda Aceh, with a total of 28 students consisting of 16 female students and 12 male students. This study used a variety of methods, including interviews and observations, to collect data. The data obtained was processed using data analysis techniques which were carried out by data reduction, data presentation and drawing conclusions. The findings of the observations indicate that the application of the Make a Match learning model in students' learning activities aligns with learning indicators. This is because the Make a Match learning model not only encourages students to work together but also to engage in active learning, giving them the chance to collaborate with friends. Emotional activities indicate that students are starting to get engaged, joyful, and eager to learn about a concept or topic during the learning process. Therefore, the Make a match learning model can be an alternative model that can be applied in the learning process in order to increase students' learning activities.